The Policy Recommendation for A Victim-Centered Approach in Human Trafficking Proceeding - Wiriyadee, Siriluck; Terdudomtham, Thamavit (Journal of Contemporary Social Sciences and Humanities, 2025)
This research examines the challenges, the personal factors influencing the needs, and cooperation of human trafficking victims to develop policy recommendation for victim-centered proceedings. A mixed-methods approach was employed, incorporating a literature review, quantitative research through questionnaires, and qualitative in-depth interviews. The hypothesis posits that victims with different personal factors have distinct needs. The study population includes 85 victims of human trafficking between September 2023 and February 2024, while 20 key informants comprise psychologists, social workers from governmental and non-governmental organizations (NGOs), and law enforcement officials. The findings indicated that victims with different personal factors mostly affect significantly different needs and cooperations. There is 8 needs which are not affected by personal factors, namely, need to seek compensation, freedom in shelter, being informed of the progression of the case, the defendant being aware of the victim’s suffering, being informed of the penalty of defendant, acknowledgment of legal proceedings, need for prevention of diseases or vaccinated, and need to express the opinion about the bail of the defendant. Factors that enhance victims’ cooperation in legal proceedings, found in quantitative research, include: (1) assurances from officials, (2) fulfillment of such assurances, (3) access to safe housing, and (4) a sense of security during testimony. Policy recommendations emerging from this research include: 1) Enhancing Sense of Security: Establishing safe environments by encouraging private sector involvement in shelter management and support services, creating secure spaces for victim interviews, strengthening witness protection laws, and ensuring victims do not encounter defendants unless necessary; 2) Streamlining Legal Procedures: Expediting legal proceedings by implementing a one-stop service model for human trafficking cases, appointing case managers to coordinate victim assistance, involving prosecutors in formulating investigative questions, and promoting pre-trial witness testimonies; and 3) Strengthening Victim Support Systems: Introducing forensic interviewers to handle case interviews professionally, increasing the number of interpreters to accommodate victims’ gender, linguistic, and national diversity, expanding the presence of psychologists and social workers, and equipping interpreters and law enforcement personnel with psychological training to mitigate victims’ emotional distress.